PENGARUH KEBIJAKAN HUTANG PADA NILAI PERUSAHAAN DENGAN GROWTH OPPORTUNITY SEBAGAI VARIABEL MODERASI - Artarini, Ni Putu Tiari; Widanaputra, Anak Agung Gde Putu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.03.TAHUN.2024, 2024)
A company that has a high growth opportunity, management will look for capital or debt as a source of company funding, so that with a company that has a high proportion of debt, investors will judge that the company has good company value, because one of the company's funding comes from bank debt. it can be indicated that the company has good company prospects so that it is sure that it can repay loans from banks in the future. This study aims to examine the effect of growth opportunity on debt policy on firm value in manufacturing companies in the food and beverage sub-sector. The population in this study is the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period. This study uses a non-probability sampling method involving 15 companies. The analysis technique used in this study is Moderated Regression Analysis (MRA), which is to test the effect of the moderating variable using an interaction test. The results show that growth opportunity is able to moderate the effect of debt policy on firm value in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2019 period.